(untitled) (De Signos y Sentidos, 2018)
The heritage and course of Córdoba’s 1918 University Reform are diverse, regarding its reception in other Latin American countries and its appropriations and re–appropriations done by different political sectors of Argentina’s University life. On one the hand, different self–defined reformist groups have seeked to justify their University principles making reference to the 1918 events as a founding political incident, anchored to the ideals of liberty and democracy; with the coming of power of Peronism, it was accused of interrupting that precious liberty. On the other hand, the first peronist administration picked up many statements of the Manifiesto Liminar, to apply according to its university policies, accusing those who wrote it to never put their own proclaims in practice. Following the study of Ciencia Nueva journal (FCEN–UBA, form April 1970 to January 1974), and utilizing methodology proposed by these magazines and newspapers, in this article we intend to discuss historiographic notions that define this alternating and irreconcilable dispute between peronism and reformism in Argentina’s University, by identifying continuities amongst peronist and reformist postulates, as well as making visible discontinuities within these movements regarding different sociohistorical contexts.